A Potential Link Between Oxidative Stress and Endothelial-to-Mesenchymal Transition in Systemic Sclerosis - Thuan, Duong Thi Bich; Zayed, Hatem; Eid, Ali H.; Abou-Saleh, Haissam; Nasrallah, Gheyath K.; Mangoni, Arduino A.; Pintus, Gianfranco (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is an autoimmune disease characterized by an aberrant immune system response, progressive fibrosis and microvasculature damage that affects organs and systems including skin, lungs, heart, digestive system, kidneys, muscles, joints, and nervous system. Several factors, including genetic and environmental, are involved in the SSc pathogenesis by leading to a pathological autoimmune response, exacerbated extracellular deposition and abnormal vascular restructuring. SSc-associated fibrosis and vascular damage can be caused by the altered secretion of growth factor and profibrotic cytokines, including transforming growth factor-beta (TGF-beta), interleukin-4 (IL-4), platelet-derived growth factor (PDGF), and connective-tissue growth factor. Such massive inflammatory response activates different biological events, including endothelial cells phenotypic conversion into activated myofibroblasts, a process known as endothelial to mesenchymal transition or EndMT. Among the multitude of proinflammatory factors involved in SSs-associated fibrosis and vascular derangement, reactive oxygen species (ROS) are paramount effectors. In this context, ROS-induced oxidative stress has been found implicated in mediating and/or activating TGF-β -induced EndMT in various diseases molecular models, suggesting the idea that a similar mechanism can be potentially involved in SSc. In this review, we collected and critically analyzed all the PubMed's articles providing experimental correlations between increased ROS generation and EndMT, as well as of the presence of the EndMT process in SSc, highlighting a potential link between oxidative stress and EndMT in this disease.